CD3 and CD20 Coexpression in a Case of Canine Cutaneous Epitheliotropic T-Cell Lymphoma (Mycosis Fungoides). (May 2016) - Brachelente, C.; Affolter, V. K.; Fondati, A.; Porcellato, I.; Sforna, M.; Lepri, E.; Mechelli, L.; Bongiovanni, L.
A 14-year-old female spayed Dachshund was presented with generalized scaling, erythema, pruritus, poor quality of hair coat, and progressive weight loss. Cutaneous epitheliotropic T-cell lymphoma (CETCL) was suspected. Skin biopsies were suggestive of CETCL. However, immunohistochemistry revealed the presence of numerous CD20+ and CD3+ cells. Clonality assay demonstrated a clonal T-cell receptor gamma rearrangement and a polyclonal IgH gene rearrangement. Double-label immunofluorescence confirmed coexpression of CD3 and CD20 by neoplastic cells. By double immunohistochemistry, neoplastic cells were CD3+ and PAX5–. The results are compatible with a CD3+, CD20+ CETCL. Coexpression of CD20 and CD3 has been recognized in peripheral T-cell lymphomas. Although documented in human CETCL, it has not been reported in canine CETCL. The pathogenetic basis of CD20 expression in mycosis fungoides is explored.